PENGEMBANGAN KONFIGURASI MODEL ANALISIS ARSITEKTUR AGILE PADA PERUSAHAAN BISNIS IT ONLINE (Studi kasus Lazada dan Bhineka.com) - RAYUNG WULAN (LPPM, 2016)
The development of company business from time to time are increasing, this factor makes the IT company interested in taking part in the industry. The Marketing Division of IT company tries hard to sell their products and services directly or indirectly. Various ways are used by the company to be able to follow the state of the arts era. Nowadays, the indirect company has come to the online business, it has been seen from many websites that are used by the online business users with their payment system and delivery order. Starts from COD (Cash Order Delivery), transfer or by using the internet banking. The more visitors visit the online business site the more favorite the site choose by them. Configuration and Architecture Agile give the reliable and flexible management that are very important for a big company to be able to survive through competition and to have quality profit. For a high class or high level company, the agile development can be described by the development method focusing on the individual and interactions software and consumer collaboration. They appreciate the unavoidable changes even the most precious software development that is the agile architecture development that can be integrated and sustained and the exact function from the system through development process. Key Words: Analysis Model, Agile Architecture, IT Business Online